2020
DOI: 10.1108/pr-08-2019-0425
|View full text |Cite
|
Sign up to set email alerts
|

High-performance work systems and job performance: the mediating role of social identity, social climate and empowerment in Chinese banks

Abstract: PurposeDespite the utility of social identity and social climate theories in explaining individual and group behaviour within organizations, little research has been conducted on how these approaches interconnect to explain the way high-performance work systems (HPWSs) may increase job performance. This study extends one’s understanding of the human resource management (HRM)–performance relationship by examining the interconnections between these disparate social approaches within the Chinese banking context.D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 68 publications
(103 reference statements)
1
23
0
Order By: Relevance
“…Despite subtle differences among HRM systems such as strategic HR management (SHRM), high-performance, high-commitment and high-involvement work systems (Becker and Huselid, 2006), high-performance work systems (HPWS) lay emphasis on both internal and external circumstances and broadly consider the key attributes of HR systems (Evans and Davis, 2005). In fact, HPWS are a way to improve individual and organizational performance via combining diverse HRM practices (Bartram et al , 2020; Beltrán-Martín et al , 2008). Given that the crucial role of HPWS accounts for organizational outcomes in general, understanding the process whereby HPWS lead to innovation outcomes is of great interest of scholars in particular.…”
Section: Introductionmentioning
confidence: 99%
“…Despite subtle differences among HRM systems such as strategic HR management (SHRM), high-performance, high-commitment and high-involvement work systems (Becker and Huselid, 2006), high-performance work systems (HPWS) lay emphasis on both internal and external circumstances and broadly consider the key attributes of HR systems (Evans and Davis, 2005). In fact, HPWS are a way to improve individual and organizational performance via combining diverse HRM practices (Bartram et al , 2020; Beltrán-Martín et al , 2008). Given that the crucial role of HPWS accounts for organizational outcomes in general, understanding the process whereby HPWS lead to innovation outcomes is of great interest of scholars in particular.…”
Section: Introductionmentioning
confidence: 99%
“…These results are in line with previous research conducted in contexts other than the Middle East. These studies found a significant link between HPWS and job performance (Bartram et al. , 2021; Zhang et al.…”
Section: Discussionmentioning
confidence: 97%
“…These results are in line with previous research conducted in contexts other than the Middle East. These studies found a significant link between HPWS and job performance (Bartram et al, 2021;Zhang et al, 2019), HPWS and OCB (Kloutsiniotis and Mihail, 2020;Pham-Thai et al, 2018;Zhang et al, 2019) and HPWS and IWB (Bos-Nehles and Veenendaal, 2019; Sanz-Valle and Jim enez-Jim enez, 2018). Moreover, work engagement was found to be positively impacted by the employees' perceptions of HPWS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the engagement at work of health professionals may indirectly contribute to their readiness to use creativity in accomplishing their tasks and to their willingness to participate in the redesign of organizational processes and practices in a perspective of continuous organizational improvement (Solstad and Petterson, 2019). Second, a positive and empowering organizational climate may mediate the effects of health professionals' engagement on individual and collective pro-innovation behaviors, enacting a social identification with the organization which fosters the commitment to organizational excellence (Bartram et al, 2020).…”
Section: Conceptual Framework and Research Hypothesesmentioning
confidence: 99%